Valorization of Okara (Soybean Pulp) as a Raw Material for Non-Flaky Crackers: Food Technology and Nutritional Evaluation - Anggraini, Anna; Pratama, Yogie; Putri, Satiti Kawuri (Jurnal Bio-Geo Material Dan Energi, 2026)
Okara, a by-product of soybean milk production, remains underutilized despite its high protein and fiber content and potential contribution to sustainable food development. This study evaluated the use of okara as a raw material in  non-flaky  crackers by examining sensory acceptance and nutritional characteristics across five wheat flour–okara ratios: 50:50, 40:60, 30:70, 20:80, and 10:90. Organoleptic assessment included color, aroma, taste, and texture, while chemical analysis measured moisture, ash, protein, fat, crude fiber, carbohydrate content, and caloric value. The formulation containing 30:70 wheat flour to okara ratio showed the most acceptable sensory quality, particularly in taste and texture. Nutritional analysis of the selected product indicated 18.23% protein, 2.40% crude fiber, 33.54% fat, 40.86% carbohydrate, 4.95% ash, 2.41% moisture, and 551.18 cal/100 g. These results demonstrate that okara can be valorized as a functional ingredient in  non-flaky crackers, improving nutritional value while supporting food waste reduction and sustainable product development for small- and medium-scale enterprises.